PERISTIWA TUTUR DUGAAN KEKERASAN SEKSUAL DI PERGURUAN TINGGI: TINJAUAN LINGUISTIK FORENSIK - Amal Akbar; Anzar Anzar; Nurcholis Nurcholis; Ilmiawan Ilmiawan (Universitas Negeri Makassar, 2023)
Events of Alleged Sexual Violence in Higher Education: A Forensic Linguistics Review. This study aims to explain speech events related to alleged acts of sexual violence, and to critically describe phenomena or events from speech events between lecturers and students. Based on the characteristics of the qualitative research used in this study, the researcher acts as a human instrument. The position of researchers in qualitative research acts as a human instrument. The data in this study were sourced from interview notes from one of the students who experienced alleged sexual assault in the campus official's office room in an unofficial situation, but the lecturer's and student's data will remain confidential to maintain the ethical dimension of each research project. The results of the study indicate that the tendency for acts of sexual violence found in this study is based on the description of the results of the speech event analysis of SPEAKING Dell Hymes so that the analysis of concurrent events can help to determine attitudes towards the position of linguistic cases so that the position of the evidence is clear.